Synthesis, Dielectric and Magnetic Characterization and Properties of Nano Magnetic Particles by using Microwave Technique - Harun Bayrakdar (Düzce Üniversitesi Bilim ve Teknoloji Dergisi)
A microwave-induced combustion method has been utilized to prepare nano-sized powders of hexagonal ferrites using urea and glycine as fuel. The dielectric and magnetic properties of these products were investigated experimentally, the dielectric properties were investigated with the RF LCR device, the magnetic properties were investigated with the Electron Spin Resonance (ESR) and Vibration Sample Magnetometer (VSM) spectrometer, and the crystalline structure was investigated with the X-ray diffraction (XRD) device.